A model of information technology capabilities towards SMES’ innovation capabilities through knowledge management - Aleneiji, Talal Mohammed (2024)
Small and medium enterprises (SMEs), especially the service sector, are pivotal to the economic growth of the United Arab Emirates (UAE), serving as the backbone of the nation's economy. Acknowledged for their substantial contributions to job creation, innovation, and economic diversification, SMEs receive support from the UAE government through policies, financial incentives, and business incubation programs. Despite these efforts, the SME service faces challenges in innovation, particularly in information technology competencies that impact knowledge management and absorptive capacity. This research addresses this gap, utilising a quantitative methodology involving 321 SME managers in the service sector. The findings reveal that information technology competencies, particularly IT infrastructure, IT integration, and IT knowledge, play a significant role in influencing innovation capabilities. The research also confirms a positive relationship between IT competencies and knowledge management, with knowledge management mediating the link between IT competencies and innovation capabilities. This study's empirical model clarifies how IT competencies empower organizations to efficiently manage and utilize their knowledge assets, consequently boosting their innovation capabilities. The study underscores the pivotal role of IT competencies as a key driver of organisational innovation, suggesting that organisations should prioritise investing in the development of these competencies. It further emphasises the necessity for organisations to adopt effective knowledge management strategies to fully capitalise on the potential of their IT investments. This study contributes to an understanding of the role of information technology competencies in enhancing innovation capabilities within SMEs. The identified linkages between IT competencies, knowledge management, and innovation provide valuable insights for organisations seeking to leverage technology for innovation in the UAE SME sector. This study proposes an empirical model that provides a practical framework for organizations to manage their knowledge assets effectively and foster innovation, thereby advancing SMEs and the UAE's economic landscape.